The Intermediation of Gold Prices in the Relationship between Macroeconomic Factors and Jakarta Islamic Index - Mohammad Khatami, Fadel; Mochamad Aziz, Roikhan (Research Synergy Foundation, 2025)
Global financial markets, including Islamic stock markets, are highly sensitive to macroeconomic conditions. Understanding the relationship between macroeconomic factors and stock indices is crucial for investors and policymakers to anticipate market fluctuations. This study examines how macroeconomic variables affect the Jakarta Islamic Index (JII). This study employs path analysis using data from January 2013 to December, with the gold price serving as the mediating variable. The results show that interest rate, exchange rate, unemployment rate, and price of gold significantly affect the Jakarta Islamic Index price index, both directly and indirectly. The consumer price index, however, only has an indirect influence on the Jakarta Islamic Index. In addition, the gold price is proven to partially mediate the association between macroeconomic factors and the Jakarta Islamic Index. All macroeconomic variables also significantly affect the gold price. This study enriches the insights of previous literature. In addition, this study provides recommendations for investors and policymakers to give more attention to macroeconomic factors that may affect the stock market.